(untitled) (Context: Journal of Interdisciplinary Studies, 2022)
The article critically examines the place of religion in modern conceptions of public space and asks whether the modern public space is “secular” in principle and what it means. Questioning the place of religious communities, traditions and claims in a public sphere clearly hinges on the conception of public sphere. The answer given will depend on the perspective we adopt, whether it is a normative perspective, a critical anthropological perspective and a philosophical-historical perspective. The article examines three answers that stand for three different perspectives and that are the following: Yes, No, and a qualified Yes. While each of perspectives defines the place of religion differently, the article retraces the evolution of a dialogue over the last twenty years. The tendency is to recognise the place of religion while adapting the notion of public sphere from secular and exclusive to post-secular and inclusive, while retaining the crucial normative aspect that public space holds for a democratic society.